Search for collectivity with azimuthal J/ψ-hadron correlations in high multiplicity p–Pb collisions at sNN=5.02 and 8.16 TeV - Acharya, S.; Adamovã, D.; Adolfsson, J.; Aggarwal, M.M.; Aglieri Rinella, G.; Agnello, M.; Agrawal, N.; Ahammed, Z.; Ahn, S.U.; Aiola, S.; Akindinov, A.; Al-Turany, M.; et al. (Elsevier, 2018)
We present a measurement of azimuthal correlations between inclusive J/ψ and charged hadrons in p–Pb collisions recorded with the ALICE detector at the CERN LHC. The J/ψ are reconstructed at forward (pgoing, 2.03 < y < 3.53) and backward (Pb-going, −4.46 < y < −2.96) rapidity via their μ+μ− decay channel, while the charged hadrons are reconstructed at mid-rapidity (|η| < 1.8). The correlations are expressed in terms of associated charged-hadron yields per J/ψ trigger. A rapidity gap of at least 1.5 units is required between the trigger J/ψ and the associated charged hadrons. Possible correlations due to collective effects are assessed by subtracting the associated per-trigger yields in the low-multiplicity collisions from those in the high-multiplicity collisions. After the subtraction, we observe a strong indication of remaining symmetric structures at ϕ ≈ 0 and ϕ ≈ π, similar to those previously found in two-particle correlations at middle and forward rapidity. The corresponding second-order Fourier coefficient (v2) in the transverse momentum interval between 3 and 6 GeV/c is found to be positive with a significance of about 5σ. The obtained results are similar to the J/ψ v2 coefficients measured in Pb–Pb collisions at √sNN = 5.02 TeV, suggesting a common mechanism at the origin of the J/ψ v2
Keywords: J/ψ correlations; p–Pb collisions; Azimuthal correlations; Elliptic flow; https://purl.org/pe-repo/ocde/ford#1.03.04